Pengaruh Kebijakan Dividen, Keputusan Investasi, Kepemilikan Manajerial, Profitabilitas, Leverage dan Ukuran Perusahaan terhadap Nilai Perusahaan - Nurhalizha Fadhilah (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2020)
The purpose of this study was to determine how the effect of dividend policy, investment decisions, managerial ownership, profitability, leverage, and firm size on firm value. research methods using quantitative research methods. The data source used secondary data obtained from the official website of the Indonesia Stock Exchange with the sampling technique using purposive sampling method. The population in the study were all companies in the Consumer Goods Industry sector listed on the Indonesia Stock Exchange during the study period from 2016-2019 as many as 59 companies with a sample size of 16 companies. The data analysis method uses panel data regression model using Eviews 8 software. The results of study indicate that dividend policy, investment decisions, managerial ownership have no effect on firm value, profitability has a significant positive effect on firm value, leverage has a significant positive effect on firm value, and size. company has a significant positive effect on firm value.